2021
DOI: 10.1002/alz.055150
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between cognitive and social leisure activities across the lifespan and neural markers for brain health: A systematic literature review

Abstract: Background: Cognitive and social leisure activities (CA/SA) as well as social network size (SNS) have been associated with performance on cognitive tasks and lower dementia risk. However, the neural mechanisms behind these associations remain unclear.Therefore, this systematic literature review aims at summarizing the available evidence on these associations across the adult lifespan.Method: MEDLINE, PsychINFO, CINAHL and the Cochrane Library of Controlled Trials were searched for potential publications until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Our results align with and extend findings from previous review and meta-analytical studies reporting small and inconsistent effects of leisure activities on WM microstructure ( Sexton et al, 2016 ; Anatürk et al, 2018 ; Duffner et al, 2023 ). One possible explanation for the selective sensitivity of the fornix, as observed in our study, may be that this major output tract of the hippocampus appears to be highly susceptible to aging processes ( Zhuang et al, 2012 ; Hayek et al, 2020 ) and environmental challenges.…”
Section: Discussionsupporting
confidence: 91%
“…Our results align with and extend findings from previous review and meta-analytical studies reporting small and inconsistent effects of leisure activities on WM microstructure ( Sexton et al, 2016 ; Anatürk et al, 2018 ; Duffner et al, 2023 ). One possible explanation for the selective sensitivity of the fornix, as observed in our study, may be that this major output tract of the hippocampus appears to be highly susceptible to aging processes ( Zhuang et al, 2012 ; Hayek et al, 2020 ) and environmental challenges.…”
Section: Discussionsupporting
confidence: 91%
“…While empirical studies on loneliness and cognitive function have shown relatively consistent results, the relationship between loneliness and brain volume remains subject to debate, with varying findings across studies (Duffner et al, 2023). Examining previous research results, a study using Framingham study data (Salinas et al, 2022) found a statistically significant decrease in total brain volume (TBV) and WMH in individuals experiencing loneliness.…”
Section: Discussionmentioning
confidence: 97%
“…This is consistent with the idea that the general factor of SES captures a constellation of risk from multiple genetically influenced traits and higher levels of SES are not protective solely due to them capturing differences in cognitive ability 10,11 . These traits could be social health factors 43 or aspects of personality linked to health, such as conscientiousness, which is phenotypically linked with lower instance of disease 44 and greater longevity 45 and shows genetic correlations with mental health traits such as MDD, ADHD, and schizophrenia 46 . Previous work examining educational attainment, an indicator of SES, identified that differences in wellbeing, health, and personality have been shown to make a contribution to the heritability of educational attainment that is independent from cognitive ability 10 .…”
Section: Discussionmentioning
confidence: 99%